1998
DOI: 10.1046/j.1432-1327.1998.2510504.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase, a chitinase, and the 39‐kDa human cartilage glycoprotein, a chitin‐binding lectin, are homologues of family 18 glycosyl hydrolases secreted by human macrophages

Abstract: In various mammals, enzymatically active and inactive members of family 18 glycosyl hydrolases, containing chitinases, have been identified. In man, chitotriosidase is the functional chitinolytic enzyme, whilst the homologous human cartilage 39-kDa glycoprotein (HC gp-39) does not exhibit chitinase activity and its function is unknown. This study establishes that HC gp-39 is a chitin-specific lectin. It is experimentally demonstrated that a single amino acid substitution in the catalytic centre of the 39-kDa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
282
0
8

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(295 citation statements)
references
References 2 publications
5
282
0
8
Order By: Relevance
“…According to Renkema et al (1998), human chitotriosidase, which is highly homologous to HC gp-39 but possesses chitinase activity, has a similar amino acid sequence in its catalytic center, the major exception being that it contains the essential Glu residue. When the Glu residue of chitotriosidase was mutated to Leu, a loss of hydrolytic activity resulted.…”
Section: Discussionmentioning
confidence: 99%
“…According to Renkema et al (1998), human chitotriosidase, which is highly homologous to HC gp-39 but possesses chitinase activity, has a similar amino acid sequence in its catalytic center, the major exception being that it contains the essential Glu residue. When the Glu residue of chitotriosidase was mutated to Leu, a loss of hydrolytic activity resulted.…”
Section: Discussionmentioning
confidence: 99%
“…7 YKL-40 is a member of the mammalian family of 18 glycosyl hydrolases. 8 -10 It is a heparin and chitinbinding lectin 10,11 without chitinase activity. 8,12 The biologic function of YKL-40 is not known in detail, but it has been shown that YKL-40 is a growth factor for connective tissue cells 13,14 and a potent migration factor for endothelial cells.…”
mentioning
confidence: 99%
“…hCHT is a phagocyte-specific chitinase that exists in two isoforms, a major 50 kDa and a C-terminally truncated 39 kDa isoform [2]. The C-terminal domain of the 39 kDa isoform has been shown to be involved in the binding of chitin [3], whereas the 50 kDa form is secreted from macrophages and the truncated form is not.…”
Section: Introductionmentioning
confidence: 99%
“…These include YKL-40 (chitinase 3-like-1), YKL-39 (chitinase 3-like-2), Ym1/2 (chitinase 3-like-3/4), oviduct-specific glycoprotein and stabilin-1-interacting chitinaselike protein [11][12][13][14][15][16][17]. YKL-40 (also termed HC-gp39 or Chi3l1) was found to be secreted, along with chitotriosidase, from activated human macrophages and it was later detected in the culture supernatant of chondrocytes, synovial cells and osteoblasts [2,11]. In vitro experiments demonstrated YKL-40 induction through the cell-stress pathway when chondrocytes were exposed to LPS (lipopolysaccharide) [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation